Konsep Penataan Permukiman yang Mendukung Pariwisata Berkelanjutan Berbasis Kearifan Lokal Pulau Lakkang - Mimi Arifin; H Hermansyah; N A Sawar; M A Fachrudin; D T Jannah; D M Ayu (Jurusan Perencanaan Wilayah dan Kota, 2021)
Lakkang Island has several tourism potentials such as natural, cultural and historical aspects where their spots merge together with the local settlement. Due to the sprawling settlement and its less development direction towards sustainability, the problems then arise. Hence, the settlement arrangements rooting for tourism are needed to control its development and to avoid the impact of losing its site-origin identity. Also, it can improve the quality of its environment and the living standards of the locals at once. The research objectives are to identify the physical and non-physical condition of Lakkang’s settlements and to analyze as well as to compile a settlement arrangement concept supporting sustainable tourism based on the local wisdom. The research data were collected through observation, interview, questionnaire, literature study, and documentation. The data are then analyzed using spatial analysis methods, descriptive qualitative and quantitative. This research provides the concept of Lakkang Island tourism development by concerning towards the 4A concept (attraction, accessibility, amenities and ancillary) as well as the arrangement of settlement facilities and infrastructure to support the quality improvement and various sustainable tourism